2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590757
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded PID controller for anaesthesia delivery

Abstract: Abstract-The technologies for continuous measurement of the anaesthetic agents circulating in body fluids are not mature yet, though some preliminary prototypes exist already. We present a control algorithm that based on the real measurement of propofol plasma concentration may adjust the delivery rate. This opens a possibility for a safer anesthesia when the technologies for online measurement of drug concentration will be mature enough to be combined with our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Therefore, recent studies are trying to address these problems to achieve comparable performance to other more advanced controllers. For instance, in [255] it is shown that the low-pass filter, included in (40), reduces the sensitivity of the derivative term to random changes. Furthermore, introducing zero reference weight for the proportional and derivative control terms (i.e.…”
Section: Automation In Anesthesiamentioning
confidence: 99%
“…Therefore, recent studies are trying to address these problems to achieve comparable performance to other more advanced controllers. For instance, in [255] it is shown that the low-pass filter, included in (40), reduces the sensitivity of the derivative term to random changes. Furthermore, introducing zero reference weight for the proportional and derivative control terms (i.e.…”
Section: Automation In Anesthesiamentioning
confidence: 99%
“…Gentilini et al (2001) present two complicated closed-loop controllers for the delivery of inhaled anesthetic isoflurane: one based on the monitoring of arterial pressure and another one of DOH through BIS. For propofol, an IV anesthetic agent often preferred to inhaled gases, an adaptive cascaded PID controller for the target driven delivery has been proposed (Simalatsar et al, 2016). The control variable is the plasma concentration of propofol.…”
Section: Related Workmentioning
confidence: 99%
“…Ren analyzed the system based on the classical control theory and proved that the cascade PID was better than the traditional single-stage PID control from an amplitude margin and a phase angle margin [29]. A cascade PID is one of the effective methods used to improve the quality of traditional PID control and it has been widely used in the field of process control [30][31][32]. For the cascade PID control of terrain-following UAVs, how to set the control feedback state quantity and how to adjust its parameters are important issues.…”
Section: Introductionmentioning
confidence: 99%